As dificuldades em trabalhar a leitura literária em sala de aula - COSTA, Mailsa Sebastiana Ferreira da (2019)
This article deals with the difficulties faced by teachers when working on literary reading in the classroom. We know that one of the greatest difficulties that teachers encounter within schools is the reading, or rather, the lack of it. Seeking to understand how and why children and young people go through various phases of schooling without building a taste for reading will surely lead to many causes. In this case, the main objective of this study is to carry out a reflection about the literary reading in the classroom in order to perceive within the educational process the main problems that prevent the formation of new readers. That is, our focus is the method of approach that predominates in public schools, their failures and contributions in dealing with work with the literary text. To do so, we will have a dialogue with some authors who have the reading as a central point in their research, such as: Lajolo (1982), Soares (2001), Freire (1995), Candido (2004) and Todorov (2009). As much as the bibliographic research base, our study aims to contribute to the expansion and the deepening of the questions that involve the mediation and the formation of new readers in the schools.